Analisis Kinerja Genset Non-Benso Sebagai Alat Penerangan Pada Daerah Yang Belum Teraliri Listrik - Harits, Caesar Abror; , Much. Djunaidi ST., MT (2016)
Genset non Benso (non Petrol Diesel) is an alternative energy that has been used in the area of Sumatra to meet household needs. However, this technology still has weaknesses, among others: (1) is still largely dependent on electrical energy as a starter equipment, (2) where all the equipment is still not efficient so it is still not portable, (3) are academically not be measured against performance Genset technology non Benso. Therefore, the purpose of this study was to modify the non Benso genset starter batteries that use this technology can be applied in areas that did not reached by electricity, and measures the comparative performance of this technology in terms of quality outcomes generated electricity. Procedural research conducted in order to achieve the purpose is data gathering, making tools, system testing, data analysis, conclusion. The data required such as motor specifications, specification generator, battery charging system, the price of each component, and comparison rpm motors and generators. The results of this study can not combine generator system with battery charging system due to excessive load on the batteries. Regardless, the results issued by the generator voltage differ significantly based on the size of the battery voltage. Voltage batteries used by 24 volts DC is able to generate 80 volts AC and 24 Volt DC. Meanwhile, if the battery voltage is 36 volts DC, the generator is able to produce 130 volts AC and 40 volts DC. It can be concluded, the greater the input voltage, the greater the output voltage. It can be powered by enlarging pulley ratio if you want to add the generator output voltage.